Manajemen Pengelolaan Dana Bos Untuk Pengupahan Guru Honorer - Risbon Sianturi; Sophia Choirotul Husniyyah; Eneng Eva Sundari; Dian Sudiana; Nisa UI (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2023)
This noble profession is the figure of a teacher because the knowledge provided by the teacher that is taught to students becomes a provision in solving problems. Therefore, the government is obliged to care for health optimally because the teacher forbids students from being prosperous in the future. The form of research is descriptive qualitative, the method researchers use to find information or research theories at certain times. The search for informants used a purposive sampling technique. Interview and documentation techniques are used as data collection techniques. Analysis of the data used is the analysis of the interaction model. The location of research was carried out at the Bantarsari State Elementary School. From the results of evaluating the use of BOS for the salaries of teachers and education staff at SD Bantarsari, it can be concluded that the use of BOS at SD Bantarsari is effective, efficient, responsive, and timely. In allocating School Operational Assistance funds to pay employees, it is in accordance with the oldest plan in the Activity Plan and School Budget and is in accordance with applicable regulations.